2023
DOI: 10.1186/s40359-023-01254-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status and related influencing factors in patients with COVID-19

Ying He,
Lei Huang,
Jian Chen
et al.

Abstract: Background The outbreak of the Corona Virus Disease 2019 (COVID-2019) has resulted in a significant number of diagnosed patients requiring treatment in designated hospitals. However, limited evidence exists regarding the prevalence of mental health problems and associated psychological factors in COVID-19 patients. Objectives This study investigated the prevalence rates of anxiety, depression, and insomnia among COVID-19 patients, as well as explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…People with a vaguely formulated sense of meaning in life, depressed and lonely may possibly be more susceptible to a severe course of the disease. It is known from health psychology that personal stress coping resources are an important element of resilience and resistance to illness (33). The personal resources for coping with stress and difficult situations play a key role in the incidence of numerous diseases, their course and prognosis (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…People with a vaguely formulated sense of meaning in life, depressed and lonely may possibly be more susceptible to a severe course of the disease. It is known from health psychology that personal stress coping resources are an important element of resilience and resistance to illness (33). The personal resources for coping with stress and difficult situations play a key role in the incidence of numerous diseases, their course and prognosis (33).…”
Section: Resultsmentioning
confidence: 99%
“…It is known from health psychology that personal stress coping resources are an important element of resilience and resistance to illness (33). The personal resources for coping with stress and difficult situations play a key role in the incidence of numerous diseases, their course and prognosis (33). Our study will not determine whether depression, loneliness and a low sense of meaning in life in the case of hospitalized people with SARS-CoV-2 are primary-the lack of resources as the cause of the disease-or secondary (severe course of the disease as the cause of depression, loneliness and low sense of meaning in life).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, little previous study has investigated the mechanisms connecting these constructs, especially when research on the mediating effect of NC between the two is not available among firefighter population. Studies have shown that higher NC scores are more likely to lead to depression [ 60 ], so this study is the first to widen the focus of the mediate effect of NC and present a more complex scenario of how SS influences DS. As a result, increasing the SS received by firefighters and reducing NC styles is of great significance for reducing the occurrence of DS in the future.…”
Section: Discussionmentioning
confidence: 99%